Phylogenomics of hyperthermophilic Archaea and Bacteria. (1st April 2004) - Klenk, H.-P.; Spitzer, M.; Ochsenreiter, T.; Fuellen, G.
Abstract : The location of hyperthermophilic organisms in the tree of life has been the source of many exciting discussions during the last two decades. It inspired not only novel hypotheses for the early evolution of the organisms, but also the isolation of many new species of Archaea and Bacteria from hot environments, as well as microbial genome sequencing and phylogenomic analyses. In view of the new wealth of genetic information generated from several analysed genomes of the hyperthermophiles, we can only conclude that the question of their exact phylogenetic location and evolutionary origin is presently as open as ever before.